Telhado de Vidro: uma reflexão sobre os processos de inventário de patrimônio imaterial do IPHAN-RJ a partir do caso do inventário da Festa de Nossa Senhora da Conceição-RJ - Carneiro, Mayra Vaz (2015)
This research analyzes the Inventory of the feast of Our Lady of Conception, at Morro da Conceição, Rio de Janeiro, done by myself for the Instituto do Patrimônio Histórico e Artístico Nacional of Rio de Janeiro (IPHAN-RJ) between July 2009 and March 2010. Using a methodology that involves documental and ethnographic research, I establish a comparison between what is officially determinated for the development of an inventory of cultural references and what is done by the technicians and researchers to the community’s demands. This work covers not only the investigation of the process of researching the inventory, but also the objective of the referred institute and the counterparts for the involved community. Still, it allows to comprehend the tactics used by the community to reach its goals with IPHAN-RJ and its researchers and, in counterpart, the strategies developed by the institution and its representatives to achieve political goals.